PENGARUH KUALITAS PRODUK, ONLINE CUSTOMER REVIEW, DAN PROMO GRATIS ONGKIR TERHADAP NIAT BELI ULANG PADA MARKETPLACE - Kharina Febby Prabowo; Kussudyarsana Kussudyarsana (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2024)
Research entitled The Effect of Product Quality, Online Customer Review, and Free Promo Ongkir on Repurchase Intention at Marketplace TikTok Shop. In this study, using quantitative analysis with purposive sampling technique. The population of this study were FEB UMS students who had bought products at the TikTok Shop marketplace. The number of samples in this study were 196 respondents. The data collection technique used a questionnaire with a Likert scale standardized using SPSS version 26 and data analysis using multiple regression analysis. The results of this study are that product quality has a positive and significant impact on repurchase intention, online customer reviews have a positive and significant impact on repurchase intention, and free shipping promos have a positive and significant impact on repurchase intention. Product quality, online customer reviews and free shipping promos simultaneously have an impact on TikTok Shop marketplace repurchase intentions